2013
DOI: 10.1111/ddi.12030
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of understanding the origin, pathways and extent of fungal invasions: global populations of the Neofusicoccum parvum–N. ribis species complex

Abstract: Aim Cryptic species in the Neofusicoccum parvum–N. ribis species complex have only recently been described, invalidating previous interpretations on host and geographical distribution. This study aimed to characterize the diversity and distribution of these species and to understand the patterns of host association, likely origins and their patterns of spread. Location Australia, Brazil, Cameroon, Chile, China, Colombia, Ethiopia, France, Greece, India, Indonesia, Iran, Italy, Japan, Kenya, Mexico, New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 59 publications
6
86
0
3
Order By: Relevance
“…ribis complex has recently been characterized (Sakalidis et al, 2013). That study confirmed the widespread and generalist pathogen status of N. parvum, which was shown to occur on 90 hosts across six continents.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…ribis complex has recently been characterized (Sakalidis et al, 2013). That study confirmed the widespread and generalist pathogen status of N. parvum, which was shown to occur on 90 hosts across six continents.…”
Section: Introductionsupporting
confidence: 66%
“…ribis complex, including N. batangarum (Begoude et al, 2010), N. occulatum and Neofusicoccum sp. karanda (Sakalidis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not expect that this pattern reflects host specificity in these cases, because all the fungi are known from previous studies to have broad host ranges. In particular, B. dothidea, L. theobromae and N. parvum are known to have extremely broad host ranges (Punithalingam 1976;Sakalidis et al 2013;. In South Africa, B. dothidea, has been reported previously from Acacia spp., Eucalyptus spp., Podocarpus spp., Syzygium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetable material included cut flowers/foliage, fresh produce, medicine/herbal treatments, nursery stock, other plant material and seeds or grain. Studies have found that vegetable material such as flower cuttings and nursery stock are important vectors of exotic species [15,16]. Timber items included bamboo, cane, rattan items, basketware, timber, wood items and willow.…”
Section: Materials and Methods (A) Exotic Species Detectionsmentioning
confidence: 99%